Efektivitas Pelatihan Empati Untuk Mereduksi Perilaku Agresi Verbal Siswa SMA Kota Makassar - Karim, Kasmayani (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. Aggressive behavior remains a persistent issue in educational settings, from elementary school through junior and senior high school. One form of aggression that frequently occurs among students is verbal aggression. The present study aims to examine the effectiveness of empathy training in reducing verbal aggression among senior high school students in Makassar. The participants consisted of 18 students selected through purposive sampling. The research employed an experimental method using a pre-experimental design, specifically a one-group pretest-posttest design. Data were collected through interviews, observations, and the Verbal Aggression Scale. Data analysis was performed using a paired sample t-test. The results showed that empathy training was effective in reducing verbal aggression among high school students in Makassar City. Students showed a decrease in verbal aggressive behavior after participating in empathy training. Keywords: Empathy Training, Senior High School, Verbal Aggression Behavior,